ANALISIS HUBUNGAN INFLASI DAN TINGKAT SUKU BUNGA DENGAN HARGA SAHAM PT. INDOFOOD SUKSES MAKMUR DI BURSA EFEK JAKARTA - Rizki Ahmad Fauzi (Jurnal Ilmiah Binaniaga, 2005)
The price of share is difficult to be predicted because influenced by various factor, like inflation, rate of interest, industrial production, investor interest to risk etc. Specially for the inflation influence and rate of interest to share, this is be required to get attention by investor  when they wish to buy or sell share  The  inflation and  rate of interest always make a move to fluctuate and influenced by national economy condition. This matter  will influence national economy wheel. After this will represent a cycle  The inflation and  rate of interest influence  the climate and enthusiasm of investment,  cost and also the company earnings, because the  inflation and  high rate of interest will kill effort industrial and commercial sector.  So that,  this matter affect also at share price. While the inflation and  the  fair rate of interest will stimulate economic wheel movement because all sector needing capital to fund  their company. So that this matter will give advantage for investor This research aim to for analyzing the relation between the  inflation and the rate of interest at the price of share by partial or the whole. Data  analysis Technique  used is  quantitative techniques that is look for the level of correlation between the inflation and the rate of interest at the price of share joined by the hypothesis test. Beside that we also use  the qualitative technique  by using characteristics and facts.  Result of analysis show  ( 1) there are negative relation and weak between  the inflation and the price of share ( 2) there are positive relation and weak between the  rate of interest  and  the price of share (3) there are positive relation  and weak between the inflation and the rate of interest with the price of share.